Juvenile rearing of Asian seabass Lates calcarifer using Demand feeding system - Mukai, Yukinori; Semail, Mohd Najmi; Nai, Han Tan (2013)
Demand feeding is a new feeding method by which fish can feed themselves. Fish switch on the feeding device when they require food. This method has several advantages because the fish can eat when they are most motivated to feed. The system can thus minimize feed loss and reduce water pollution. The demand feeding system has been studied for ten years, but so far, there are only a few commercialized feeding devices. Currently, the most urgent issue facing the aquaculture industry in Malaysia is seed production, especially, groupers. Asian seabass Lates calcarifer also known as barramundi is an economically important fish species in Southeast Asian countries.